2018
DOI: 10.1590/s1677-5538.ibju.2017.0506
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PSA density of transition zone as a potential parameter in reducing the number of unnecessary prostate biopsies in patients with PSA levels between 2.6 and 10.0 ng/mL

Abstract: Purpose:To assess the accuracy of prostate-specific antigen (PSA) adjusted for the transition zone volume (PSATZ) in predicting prostate cancer by comparing the ability of several PSA parameters in predicting prostate cancer in men with intermediate PSA levels of 2.6 – 10.0 ng/mL and its ability to reduce unnecessary biopsies.Materials and Methods:This study included 656 patients referred for prostate biopsy who had a serum PSA of 2.6 – 10.0 ng/mL. Total prostate and transition zone volumes were measured by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…PCa usually arises from the PZ, and most BPH originates in the TZ. [10, 12] Our result are consistent with this opinion. Compared with patients without PCa, lower TZV (12.35 vs 32.14 ml, P <0.001) and higher PZV (32.9 vs 27.79 ml, P <0.001) was found in patients with PCa, which indicates the diagnostic potential of TZV and PZV for diagnosing PCa.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…PCa usually arises from the PZ, and most BPH originates in the TZ. [10, 12] Our result are consistent with this opinion. Compared with patients without PCa, lower TZV (12.35 vs 32.14 ml, P <0.001) and higher PZV (32.9 vs 27.79 ml, P <0.001) was found in patients with PCa, which indicates the diagnostic potential of TZV and PZV for diagnosing PCa.…”
Section: Discussionsupporting
confidence: 92%
“…PSA mainly leaks from the TZ. [10, 12] Therefore, we hypothesized that prostate-zone adjusted PSA serves as a more effective parameter than PSAD and PSA for the diagnosis of PCa, which is consistent with published studies. For example, a study of 1712 patients who underwent TRUS-guided prostate biopsies found that the AUC of PSADTZ is 0.766 and those of PSAD and PSA are 0.749 and 0.585, respectively, for diagnosing PCa.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…1 ). At the conclusion of screening, 11 studies (one in Korean) were included in this systematic review [ 13 14 15 16 17 18 19 20 21 22 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used marker in the diagnosis of prostate cancer is PSA [2]. The upper limit for gray-zone PSA has been determined as 10 ng/ml in numerous studies [6][7][8]15,[17][18]. Some other studies, though few in number, suggest that the upper limit for gray-zone PSA may show ethnic variation and propose that this limit is likely to be higher in countries where PCa is less common, particularly in Far Eastern countries [9,19].…”
Section: Discussionmentioning
confidence: 99%